La cultura tributaria y su relación con la evasión fiscal de los comerciantes del Mercado Zonal Palermo (Ex Mayorista), distrito de Trujillo, Año 2018 - Villalobos Alcántara, Thalía Luzmila (2018)
The main objective of this research is to determine the relationship between the Tax Culture and Tax Evasion of the Zonal Market merchants Palermo (Ex Mayorista), district of Trujillo, 2018. The problem that arises in the present work seeks to answer the following question: How is the tax culture related to the tax evasion of the Mercado Zonal Palermo merchants (ex Mayorista), Trujillo district, 2018? The hypothesis formulated maintains that the Tax Culture has an inverse relationship with the Tax Evasion of the traders of the Zonal Market Palermo (ex Mayorista), district of Trujillo, year 2018. The present investigation has a non-experimental character, to develop it we used primary sources obtained through surveys, which has allowed us to obtain data for further analysis. It is concluded that there is no clear evidence of an inverse relationship between the Tax Culture and Tax Evasion in the traders of the Zonal Market Palermo (Ex Mayorista), district of Trujillo, 2018. This is due to the contradictions incurred by the merchants contrast their answers to the responses of customers who come to their establishments.